Barriers and disparities in preventive oral health care in the UK: insights from oral health professionals and consumers surveys - Michelle Wodke; Munisha Mangal; Alyson Axe; Billy Franks; Kate Fabrikant (BDJ Open, 2026)
Abstract Objective/Aim Preventive oral health care (POHC) is an integral aspect of overall health, yet oral health professionals (OHPs) frequently encounter challenges with patient adherence to preventive recommendations. This study aims to identify barriers to effective POHC implementation examining perspectives from both consumers and OHPs. Understanding these barriers will support targeted interventions to enhance public awareness and promote proactive oral health behaviours. Materials and methods Two UK-wide research surveys were conducted to capture oral health habits and the integration of preventive advice during routine dental visits. The first survey targeted OHPs ( n = 505) and consumers ( n = 2000), exploring attitudes toward POHC and compliance. The second survey involved parents ( n = 1004) and children ( n = 1004) to assess parental influence on paediatric oral health practices. Results Findings revealed notable variations in attitude towards POHC in consumers across demographics, including gender-based differences. Additionally, a misalignment between consumer expectations and OHPs perceptions was observed. Children and parent survey results further highlighted that parental awareness and attitudes substantially influenced children’s preventive behaviours and confidence, with notable regional variations. Conclusion This research highlights the need to involve both consumers and OHPs to improve POHC for better outcomes in oral health. There is an opportunity for the oral health industry to address the identified barriers through tailored consumer-facing educational campaigns and support relevant training programmes, ensuring that all OHPs are better equipped. These efforts could build a foundation for improved quality of life and lifelong oral health in the UK.